2000
DOI: 10.1103/physrevb.62.r763
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and superconductivity in underscreened Kondo chains

Abstract: We present a one dimensional model of electrons coupled to localized moments of spin S ≥ 1 in which magnetism and superconductivity interplay in a nontrivial manner. This model has a nonFermi liquid ground state of the chiral spin liquid type. A non-conventional odd-frequency pairing is shown to be the dominant instability of the system, together with antiferromagnetism of the local moments. We argue that this model captures the physics of the Kondo-Heisenberg spin S = 1 chain, in the limit of strong Kondo cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Nominally, in this material the nickel valence is 3+, i.e. 3d 7 , which would suggest a model with a single electron in the cubic e g doublet, a two-fold orbital degeneracy. However, another interpretation is that the nickel valence is actually 2+, with an additional hole per nickel spread out amongst the oxygen ions, 2 analogous to the Zhang-Rice singlet in cuprates.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nominally, in this material the nickel valence is 3+, i.e. 3d 7 , which would suggest a model with a single electron in the cubic e g doublet, a two-fold orbital degeneracy. However, another interpretation is that the nickel valence is actually 2+, with an additional hole per nickel spread out amongst the oxygen ions, 2 analogous to the Zhang-Rice singlet in cuprates.…”
Section: Introductionmentioning
confidence: 84%
“…Because each nickel thereby has an S = 1 spin and is accompanied by only a single oxygen hole with S = 1/2, this takes the form of an underscreened Kondo lattice model. 7,8 To enable the DMRG analysis, we take this model to be one dimensional. Though this is obviously a drastic approximation, our model retains the underscreened Kondo physics, and has the symmetries to allow charge ordering of the same type observed in the nickelate materials.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting UV-IR transmutation can be analysed from the conservation of the su(2) spin and one has the following correspondence [21,54]:…”
Section: The Uv-ir Transmutation Of the Fieldsmentioning
confidence: 99%
“…Finally, one should note that the scaling dimensions of the physical observables of the two-channel KHL obtained by the Toulouse point solution coincide with those of the recent CFT approach. 15 In this respect, we stress that, in contrast with the latter approach, the Toulouse point solution enables us to take into account the inherent velocities anisotropy in the problem. In summary, we have shown that the two generalizations of the one-dimensional KHL considered in this paper exhibit a nontrivial non-Fermi-liquid low-temperature phase belonging to the class of chirally stabilized fluids with strong enhanced staggered composite pairing correlations.…”
Section: ͑9͒mentioning
confidence: 99%